HENRY THE STEINWAY AND THE PIANO RECITAL - Coveleskie, Sally; Goodrich, Peter; Friedman, Laura (Chicago, Illinois : GIA Publications, Inc., 2020)
Ana is not ready to play in the piano recital, but Henry the Steinway helps her prepare.
Keywords: Americans Fiction; Children's stories; Concerts -- Fiction; Piano -- Fiction